Advancement of food‐derived mixed protein systems: Interactions, aggregations, and functional properties. Issue 1 (15th December 2020) - Wu, Chao; Wang, Tao; Ren, Chao; Ma, Wuchao; Wu, Di; Xu, Xianbing; Wang, Li‐Shu; Du, Ming
Abstract: Recently, interests in binary protein systems have been developed considerably ascribed to the sustainability, environment‐friendly, rich in nutrition, low cost, and tunable mechanical properties of these systems. However, the molecular coalition is challenged by the complex mechanisms of interaction, aggregation, gelation, and emulsifying of the mixed system in which another protein is introduced. To overcome these fundamental difficulties and better modulate the structural and functional properties of binary systems, efforts have been steered to gain basic information regarding the underlying dynamics, theories, and physicochemical characteristics of mixed systems. Therefore, the present review provides an overview of the current studies on the behaviors of proteins in such systems and highlights shortcomings and future challenges when applied in scientific fields.